Study on the semiconductor wafer fabrication performance improvement based on job release control - Andy Darwin Kasan Hidayat (2008)
Mean cycle time, standard deviation of the cycle time, WIP level, throughput, and due date performance are the main performance measurements of factory. In this project, the investigation of the production control will be conducted. The extension of WIPLOAD control mechanism will be adopted to study the improvement of those measured parameters. The performance will also be compared with the other production control mechanisms such as CONWIP. In this research real factory data from a semiconductor wafer fabrication was used to construct the model and to conduct the analysis. A simulation based model was adopted in conducting our experiment. A new perspective of WIPLOAD control dubbed WIPL-n-Ctrl was presented in this report. Factory performance with more than one WIPL-n-Ctrl was also simulated in this research. Results indicated that WIPL-n-Ctrl is able to outperform existing WIPLOAD control. Additional WIPL-n-Ctrl is also found to be effective only when it is in front of the bottleneck machine. In addition, this research also found out that there is trade off between average cycle time and standard deviation of cycle time when WIPL-n-Ctrl was incorporated with different dispatching rules.